Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Konsumen Mcdonald’s Darmo Surabaya - Agnes Martalina Gasmi; Harsono Teguh; Achmad Daengs GS; Bambang Karnain; Sugiharto Sugiharto; Rina Dewi; I Gede Wiyasa (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to see the effect of service quality on customer satisfaction at McDonald Darmo Surabaya. This type of research is quantitative with information described in the form of numbers as a tool to obtain information regarding what is known. The population used is McDonald Darmo Surabaya consumers with a sample of 100 people determined through the use of purpsove sampling. The results obtained show that service quality significantly affects customer satisfaction at McDonald Darmo Surabaya, through the t test obtained a sig value of 0.000 (<0.05) which indicates the hypothesis for service quality at McDonald Darmo Surabaya has a significant effect on customer satisfaction at McDonald Darmo Surabaya is accepted. Then through the coefficient of determination test, a value of 0.720 or 72.0% is obtained which reflects the dimensions of service quality in influencing consumer satisfaction, namely 28%, while the rest is influenced by external variables.